Digitally assessing social–emotional skills in early school years: initial validation of a screening instrument - Kogler, Andrea; Gasteiger-Klicpera, Barbara; Prinz, Katharina; Paleczek, Lisa (Frontiers in Psychology, 2025)
IntroductionSocial–emotional skills are essential in everyday interaction and develop in early and middle childhood. However, there is no German instrument to help primary school students identify their strengths and weaknesses in different social–emotional skills that does not rely on written language. This paper introduces a new digital instrument, the GraSEF: Grazer Screening to assess Social–Emotional Skills, which was developed to measure (1) Behavior in Social Situations, (2) Prosocial Behavior, (3) Emotion Regulation Strategies, (4) Emotion Recognition and (5) Self-Perception of Emotions using different test formats (e.g., situational judgement test, self-assessment, performance tests). In the GraSEF, students work through an online survey tool, using audio instructions to guide them through the test.MethodsThe present study analyses the responses of second graders (Mage = 8.23 years, SDage = 0.48, 48% female). The intention was to gain initial insight into the instrument’s psychometric quality and user-friendliness.ResultsIn general, the instrument was found to have acceptable to good internal consistency, sufficient discriminatory power and item difficulty. However, one subtest (5: Self-Perception of Emotions), as well as three situations of the situational judgment test (1: Behavior in Social Situations), were excluded due to unsatisfactory fit and distribution. The validity check revealed low to moderate correlations between teacher rating and student scores. On average, students completed the screening in about 30 min and provided positive feedback regarding usability.DiscussionWhile the small sample size only provides preliminary insight into the instrument’s psychometric quality, the results suggest that the GraSEF can reliably measure various dimensions of social–emotional skills in second graders, even among those with low reading skills.